Dynamic real-time IP-based publish-subscribe group collaboration using multicast label filters - Singh, Jaipal; Veeraraghavan, P.; Singh, S. (IEEE, 2009)
Internet based enterprise level collaboration tools enable organisations to make decisions faster and more accu-rately with less effort. However, these tools provide limited real-time group collaboration within and across organisations. This paper proposes a novel IP network layer filter architec-ture that provides efficient and scalable real-time group col-laboration between the required entities within an organisa-tion. This proposed network architecture uses a label filter mechanism to improve privacy, scalability and bandwidth for one-to-one, one-to-many and many-to-many real-time com-munication on an existing multicast group in an organisation.